On the Road to Better Life? Rural Road and Economic Development in Albania - Santosh Kumar Gautam; Ermal Ilirjani; Patralekha Ukil (Institute of Labor Economics (IZA), 2025)
This study evaluates the impact of investment in rural roads on household welfare in Albania. Using a difference-in-differences method, we find that treated households experienced a 35-percentage point increase in the quality of roads relative to control households and reduced travel times to the nearest motorable roads. The study also demonstrates that the price and value of residential and farmland increased in the treated communities. Household heads in treated communities were less likely to be unemployed, and there was a higher incidence of self-employment in treated households, which seems to suggest a pattern of households shifting away from paid employment to self-employment in response to improved economic opportunities due to improved connectivity. The study does not find a significant effect on household income, but finds an increase in consumption expenditure. In general, these findings indicate that investments in rural roads have had positive impacts on the welfare of the family in Albania.
Keywords: O12; O18; 330; rural roads; income; food expenditure; Albania